Comparison of nutrient contents of wild and farmed rainbow trout (Oncorhynchus mykiss, Walbaum 1792) from Keban Dam Lake in Eastern Anatolia region of Turkey - Ozcicek, Esin; Can, Erkan; Yilmaz, Okkes (Wiley, 2022)
In this study, fatty acids, fat-soluble vitamins (A, D, E, K vitamins) and cholesterol contents of wild-caught and farm-raised rainbow trout (Oncorhynchus mykiss) were compared. The amounts of docosahexaenoic acid (22:6 n-3, DHA) in wild and farmed forms were 21.56%-18.14%, 18.79%-16.21% and 14.34%-11.49% in April, May and June, respectively. Vitamin E, which is one of the fat-soluble and antioxidant vitamins, showed highest level among the vitamins. Vitamin E levels in both wild and farmed fish were 5.11-4.26, 4.83-2.89 and 0.99-1.95 mg/100 g in April, May and June, respectively. The substantial difference between wild and farmed rainbow trout was found in May (p < 0.05). In conclusion, both wild and farmed rainbow trout from Keban Dam Lake (Pertek Region) can be considered as good sources of n-3 polyunsaturated fatty acids (PUFA). However, it was observed that the n-3 PUFA level in wild form was higher than the culture fish within the investigated monthly periods. On the other hand, farmed fish demonstrated higher levels of n-6 PUFA over the wild individuals.
Keywords: cholesterol; fatty acid; Oncorhynchus mykiss; rainbow trout